An investigation on the expenditure and number trained by big companies in South Africa - Surgey, Gavin George (My University, 2011)
This paper investigates the nature of company investment in training. A survey was undertaken in 2007 of 106 large companies operating in South Africa to examine the size of expenditure on training by these firms, the beneficiaries of the training; and investigate firms’ attitudes towards such programmes. Both the level of firm spending, and the proportion of payroll it amounts to are significant. The study reveals that businesses are acutely aware of the risks of skills shortages and their role in mitigating the risks to themselves. It also finds that investment into training and development is directly and largely driven by a need to increase productivity, profitability, and sustainability as companies try to proactively address a lack of skilled labour.
Keywords: Training; Development